Comparison of littoral and deep water sampling methods for assessing macroinvertebrate assemblages along the longitudinal profile of a very large river (the Danube River, Europe). (2nd July 2019) - Szekeres, József; Borza, Péter; Csányi, Béla; Graf, Wolfram; Huber, Thomas; Leitner, Patrick; Milosević, Djuradj; Paunović, Momír; Pavelescu, Claudia; Erős, Tibor
Abstract: We comparatively examined the role of littoral and deep water sampling methods in assessing macroinvertebrate assemblages and in characterizing longitudinal changes in assemblage structure along >2, 500‐km–long course of the Danube River, Europe. The effectiveness of detecting taxa corresponded well with an inshore–offshore gradient in sampling (i.e., distance from shore). Nevertheless, each method (i.e., littoral multihabitat sampling, kick and sweep sampling, and deep water dredging) contributed to some degree to overall taxa richness and species composition. Sampling in different depth zones characterized different assemblages, and consequently, inshore–offshore position was at least as important determinant of assemblage structure as longitudinal position of sampling sites in the river. Although we found significant congruency in the spatial variability of assemblages among the sampling methods, the relationships were only moderate. Our study on the large Danube River confirms studies from smaller rivers in other geographic regions that littoral monitoring provides higher taxa richness and more responsive changes to longitudinal gradients than deep water samples. Nevertheless, it also shows that sampling in different depth zones provides supplementary information on assemblage structure. Understanding changes in macroinvertebrate assemblages related to differences in sampling method is crucial to improve the bioassessment and environmental management of large rivers.